Leveraging Positive Social Environments: Instructional Leadership Strategies for Building Caring Learners - Millatul Islamiyah; Ida Nur Rahma Wati; Muhammad Pirlo Al Ghifary; Nur Qomari; Mardiyah (Ambarsa : Jurnal Pendidikan Islam, 2026)
This study aims to investigate teacher instructional leadership strategies in leveraging positive social environments to foster caring characters among learners. Despite growing emphasis on academic excellence, contemporary educational settings frequently struggle with character deficits and low empathy among students, creating a critical gap in holistic student development. Utilizing a qualitative multi-site case study design, this research gathered empirical data from three distinct educational institutions. Data were collected through in-depth semi-structured interviews, classroom observations, and institutional document reviews involving school principals, teachers, and student representatives. The accumulated data were then analysed using a multi-site thematic analysis framework, which involved interactive data reduction, data display, and conclusion drawing. The findings reveal that instructional leaders effectively build caring characters by deliberately embedding prosocial values into the daily curriculum. Teachers successfully cultivate empathy by establishing collaborative classroom norms that encourage peer-to-peer support. And the optimization of a positive social environment is achieved through structured peer-mentoring programs that bridge diverse student backgrounds. The study demonstrates that modelling empathetic behaviour by educators serves as a primary catalyst for student behavioural transformation. Additionally, integrated school-community engagement initiatives significantly reinforce the sustainability of students' caring habits outside the classroom. Future research should consider a longitudinal quantitative approach to measure the long-term statistical impact of these social environmental strategies across larger, national-scale student populations.